An unusual inguinal hernia presentation in an infant: Amyand's hernia with acute appendicitis - Arslan Alıcı, Çiğdem (Journal of Surgery and Medicine, 2019)
Amyand's hernia is a rare condition defined as the presence of appendix vermiformis within the hernia sac, and it constitutes 1% (0.19-1.7%) of all inguinal hernias. Inflammation of the appendix within the inguinal sac is rarer, comprising 0.1% (0.07-0.13) of all Amyand’s hernia cases. Although the clinical presentation of the disease varies depending on the inflammation of the appendix, the diagnosis is usually made during the operation. We herein present a 2-month-old male patient who underwent appendectomy during right inguinal herniotomy after visualization of the inflamed appendix adhering to the wall of the hernia sac.